Analisis Implementasi ISO 31000:2018 sebagai Kerangka Strategis Pengelolaan Risiko: Studi Kasus pada BPJS Ketenagakerjaan - Iswardhani, Indri; Sandira, Nur Fadilah Ayu; Sarah, Nulthazam (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
This study analyzes the implementation of ISO 31000:2018 as a strategic framework for risk management at BPJS Ketenagakerjaan during the period 2020-2023. ISO 31000:2018 provides guidelines for designing and managing risks systematically, which is crucial for organizations managing social security funds like BPJS Ketenagakerjaan. This research employs a qualitative approach using secondary data obtained from the annual integrated reports of BPJS Ketenagakerjaan during the study period. The findings indicate that BPJS Ketenagakerjaan has successfully identified, analyzed, and managed risks more effectively through the implementation of ISO 31000:2018. This is reflected in the improved management of various risk categories, including strategic risk, market risk, liquidity risk, credit risk, operational risk, reputational risk, information technology risk, legal risk, and compliance risk. Additionally, the increase in the risk maturity value from 2.82 in 2020 to 3.94 in 2023 indicates that BPJS Ketenagakerjaan has become more mature in its risk management practices. This study also provides recommendations for future research, such as in-depth analysis of specific risk categories and the use of new technologies in risk management.